The Sleep of Shelter Dogs Was Not Disrupted by Overnight Light Rather than Darkness in a Crossover Trial - Houpt, Katherine A. (Animals (Basel), 2019)
SIMPLE SUMMARY: Dogs are often left unattended overnight in shelters. This has led shelter mangers to worry that the dogs were suffering from separation anxiety and, therefore, exhibiting stereotypic or repetitive behaviors such as pacing, barking or digging at exits. Mangers also worried that dogs exposed to light at night were not able to sleep or slept less because some areas of the shelter were lit for security reasons. The ten dogs in this study were walked twice daily and provided with many enrichment devices and music during the day. They were housed in individual rooms each with a window allowing visualization of the dog by the public and vice versa. The dogs slept 10.8 h/night when in darkness and 10.5 h/night when their pens were lightened; there was no significant difference. They exhibited no stereotypic behaviors. They slept in bouts of slightly less than an hour, arising after each bout to stand up and then lie down again. Apparently, these well-stimulated shelter dogs slept soundly in the absence of people. ABSTRACT: Dogs in shelters may be unattended at night. The purpose of this study is to describe the night-time behavior of dogs in a shelter and to determine if artificial light affected their sleeping patterns. Ten dogs were video-recorded under both light and dark conditions and their behavior recorded using focal animal sampling. The dogs were lying down 649 ± 40 min (mean ± SD) in the light condition and 629 ± 58 min in the dark condition each night. They awoke, stood up, turned around and then lay down again every 48 to 50 min. There was no significant difference in time spent lying between the two conditions (p > 0.05). Light did not seem to affect their behavior. The conclusion is that dogs in shelters may sleep in the absence of people and that light does not disrupt their sleep patterns.